الزراعة في الجزائر وأثرها على النمو الاقتصادي للفترة 1991-2022 - بن علي،الطاهر; بوبكر،حوامدي; سليم،بوخلط (university of eloued جامعة الوادي, 2024)
تهدف هذه الدراسة إلى اظهار العلاقة بين الزراعة والنمو الاقتصادي في الاقتصاد الجزائري خلال الفترة 1991- 2022والمنهج المتبع هو المنهج الوصفي التحليلي، ولتحليل هذه الظاهرة وهذا بناءاً على الأساليب القياسية الحديثة المستخدمة في القياس الاقتصادي والمتمثلة أساسا في اختبارات الاستقرارية ونظرية التكامل المشترك، وقد استخدم الناتج المحلي الاجمالي كمؤشر للنمو الاقتصادي واستخدم الإنتاج الزراعي كمؤشر للزراعة، ومن أجل هذا سنتعرف على الطريقة التي تقوم على أساسها هذه الدراسة وهي تتمثل في""نموذج الانحدار الذاتي للابطاء الزمني الموزع ARDL""ARDL-AUTO-REGRESSIEV DISTRIBUTED LAG MODELS واختبار السببية ونموذج تصحيح الخطا. ECMوذلك بالتعرف عليها في طرق تقديرها ومعالجتها وفق منهجية الدراسة الخاصة بالسلاسل الزمنية. ولقد أوصت الدراسة على الاهتمام بقطاع الزراعة وذلك من قبل الدولة في دعم المستثمرين في هذا القطاع This study aims to demonstrate the relationship between agriculture and economic growth in the Algerian economy during the period 1991-2022. The approach used is the descriptive and analytical approach، and to analyze this phenomenon، based on modern standard methods used in economic measurement، which are mainly represented in stability tests and cointegration theory. The result was used GDP is an indicator of economic growth and agricultural production is used as an indicator of agriculture. For this purpose، we will learn about the method on which this study is based، which is represented by the “ARDL-AUTO-REGRESSIEV DISTRIBUTED LAG MODELS” model Causality testing and error correction model (ECM). by getting to know it in the ways of estimating and treating it. According to the time series study methodology. The study recommended that the state pay attention to the agricultural sector in supporting investors in this sector.
مذكرة ماستر اقتصاد
Keywords: النمو الاقتصادي; الإنتاج الزراعي; الناتج المحلي الاجمالي; ARDL; ECM; economic growth; agricultural production; gross domestic product